Pegawai Loyal Sebagai Pelaku Fraud : Perspektif Hexagonal - Wiasti, Ika Anggie; Leniwati, Driana; Juanda, Ahmad (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research Objectives : This research focuses  on the analysis of loyal employees as fraud perpetrators: a hexagonal perspective. Design / Method / Approach : A qualitative, case-study approach focused on a state-owned bank in East Java. Search results : The search results  of 6 indicators are 4 indicators that affect the performance of loyal employees in committing fraudulent acts, namely pressure, ability, opportunities and rationalization. Theoretical contribution/originality : This study shows that  employees who are loyal in committing fraud by utilizing their skills and experience on the job and the average employee who performs this action are employees of high standing such as managers and branch heads who have the ability to obtain higher education as they do by neglecting the duties and authority of management so that they do not work effectively in terms of combating fraud. Practical implications : This analysis is used to analyze fraud that occurs in loyal employees. Research limitations : The limitations of this study use the hexagonal perspective only.